Management of critical parameters of logistics and infrastructure projects by means of computer experiment (on the example of the security and defense sector in war conditions) - Kobylkin, Dmytro; Zachko, Oleh; Mytsko, Rostyslav; Zakharchyshyn, Serhiy; Elmas , Chetin (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of the research in the article is the management of critical parameters of infrastructure and logistics projects using the example of the security and defense sector in wartime by means of computer experiments using modern artificial intelligence tools, in particular multi-agent systems. The purpose of the study is to conduct a computer experiment to study the critical parameters of the functioning of infrastructure and logistics projects based on intelligent models that apply the theory of multi -agent systems. The article solves the following tasks: formalization of technical parameters of transport infrastructure; formalization of the subject area of logistics and infrastructure project management, modeling of critical parameters of the functioning of infrastructure and logistics projects under martial law, risk assessment of logistics and infrastructure projects based on the analysis of critical locations. The following methods are used: operations research methods; computer modeling methods, artificial intelligence technologies, in particular multi-agent systems; risk theories. Research results: the methodology for conducting a computer experiment modeling critical parameters of the functioning of infrastructure and logistics projects under martial law was considered. The implementation of logistics projects was analyzed depending on such criteria as distance, project time, load capacity, critical zones of logistics projects and qualitative benefits from implementation. A matrix of logistics project routes under martial law was developed. A qualitative and quantitative analysis of the risks of logistics and infrastructure projects under martial law was conducted. Conclusions: the obtained scientific results complement the methodology of infrastructure project management and make it possible to implement logistics projects under martial law and the worsening of the food security situation, in particular as alternatives to the Black Sea Grain Initiative, as well as infrastructure and logistics projects in the security and defense sector under war conditions. The results obtained can also be applied in planning logistics projects for the supply of weapons under martial law.